Severe Contralateral Striatal Hypometabolism in a Case of Diabetic Nonketotic Hyperglycemic Hemichorea on 18F-FDG PET/CT Brain. (February 2020) - Kumar Vadi, Shelvin; Mehta, Sahil; Kumar, Rajender; Tandyala, Naresh; Singh, Harmandeep; Mittal, Bhagwant Rai
Abstract : Abstract: Chorea induced by diabetic nonketotic hyperglycemia is a rare and poorly understood entity with a favorable prognosis after correction of the hyperglycemia. We present a case of elderly diabetic woman with poorly controlled blood glucose levels, presenting with choreiform movements limited to the right side. 18 F-FDG PET/CT showed marked hypometabolism in the basal ganglia contralateral to the side with hemichorea. The metabolic dysfunctions lead to nonketotic hyperglycemic chorea, although poorly understood; the index case demonstrated severe glucose hypometabolism in the striatum and adds to the other reported differential diagnoses for striatal hypometabolism.